Analysis of Critical Thinking Skills of Elementary School Students Through Integrated Problem-Based Learning Model with Mind Mapping - Nurfadila MY; Nurlina Nurlina; Ma’ruf Ma’ruf (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Background of the rearch is the low critical thinking skills of students. In addition, there is no data related to the distribution of indicators of students' thinking skills, especially in science learning. The research objective was to analyze the critical thinking skills of elementary school students through an integrated problem-based learning model with mind mapping. This type of research is experimental research with a quantitative approach. The research design used was a pre-experimental design of the One-Group Pretest-Posttest Design. The population in this study was class V SDI BTN IKIP I Makassar City. In this study using a purposive sampling technique this study used a purposive sampling technique. Data collection in this study was a descriptive test consisting of 7 questions according to indicators of critical thinking ability. The results of this study are that the basic clarification indicator gets the highest score on the pretest and posttest, with an average score of 60 and 82. Meanwhile, the strategy and tactics indicator receives the lowest score, averaging 52 on the pretest and 75 on the posttest. So it means that the distribution of critical thinking skills indicator scores shows that the basic clarification indicator gets the highest score, and the strategy and tactics indicators get the lowest score.